A condition-based maintenance model for a three-state system subject to degradation and environmental shocks. (March 2017) - Yang, Li; Ma, Xiaobing; Zhao, Yu
Highlights: A new maintenance model is established based on a three-state degradation and external environmental shocks. The influence of system state on the internal-based degradation as well as fatal shocks is considered. Two different preventive thresholds are arranged to cut down the maintenance cost. A cost comparison between the proposed policy and the constant threshold policy is conducted for validation. Abstract: Condition-based maintenance (CBM) is a key measure in preventing unexpected failures caused by internal-based deterioration and external environmental shocks. This study proposes a condition-based maintenance policy for a single-unit system with two competing failure modes, i.e., degradation-based failure and shock-based failure. The failure process of the system is divided into three states, namely, normal, defective and failed, and a defective state incurs a greater degradation rate than a normal state. Random shocks arrive according to a non-homogenous Poisson process (NHPP), leading to the failure of the system immediately. The occurrence of external shocks will be affected to the degradation level of the system. Periodic inspections are performed to measure the state and the degradation level of the system, and two preventive degradation thresholds are scheduled depending on the system state. The expected cost per unit time is derived through the joint optimization of the two preventive thresholds as well as the periodic inspection interval. A numerical example is proposed to illustrate the maintenance model.